2021
DOI: 10.1126/sciadv.abe9256
|View full text |Cite
|
Sign up to set email alerts
|

Warming and elevated ozone induce tradeoffs between fine roots and mycorrhizal fungi and stimulate organic carbon decomposition

Abstract: Climate warming and elevated ozone (eO3) are important climate change components that can affect plant growth and plant-microbe interactions. However, the resulting impact on soil carbon (C) dynamics, as well as the underlying mechanisms, remains unclear. Here, we show that warming, eO3, and their combination induce tradeoffs between roots and their symbiotic arbuscular mycorrhizal fungi (AMF) and stimulate organic C decomposition in a nontilled soybean agroecosystem. While warming and eO3 reduced root biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 78 publications
(121 reference statements)
2
36
0
Order By: Relevance
“…Deveautour et al (2018) also found that SRL was positively correlated with AMF richness and the fine to coarse root length ratio was correlated to AMF community composition. Also, Qiu et al (2021) recently showed that warming significantly increased SRL, but reduced root length colonized by AMF in a non‐tilled soybean system, indicating a trade‐off between plant root traits and AMF. Together, these results suggest that warming and altered rainfalls may alter nutrient availability and root traits, thereby indirectly influencing abundance and community composition of the AMF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deveautour et al (2018) also found that SRL was positively correlated with AMF richness and the fine to coarse root length ratio was correlated to AMF community composition. Also, Qiu et al (2021) recently showed that warming significantly increased SRL, but reduced root length colonized by AMF in a non‐tilled soybean system, indicating a trade‐off between plant root traits and AMF. Together, these results suggest that warming and altered rainfalls may alter nutrient availability and root traits, thereby indirectly influencing abundance and community composition of the AMF.…”
Section: Introductionmentioning
confidence: 99%
“…Also, warming often stimulates microbial growth and enhances soil mineralization, nitrification, and thus nitrogen (N) availability (Rustad et al, 2001; Zhang et al, 2020). High N availability in soil can in return reduce plant dependence on AMF for N uptake, and thus decrease AMF biomass and alter AMF community composition in favor of the species with less extensive extraradical hyphal networks (Qiu et al, 2021; Treseder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated carbon dioxide (CO 2 ) and temperature could affect plant utilization and the acquisition of Pi and management to maintain ecosystem sustainability in P-deficient regions by increasing the rate of decomposition in soil, stimulate photosynthesis, and subsequent growth responses (Jin et al, 2015;. Elevated CO 2 and/or temperatures may alter P acquisition through changes in root morphology and increases in rooting depth (Qiu et al, 2021). Furthermore, the quantity and composition of root exudates are likely to change under elevated CO 2 , and/or temperatures may affect the carbon fluxes along the glycolytic pathway and the tricarboxylic acid cycle (Zayas-Santiago et al, 2020).…”
Section: Biotic Factorsmentioning
confidence: 99%
“…Such trait-based approaches have increasingly been used to probe alterations in belowground communities (Han et al 2020;Spitzer et al 2021). For example, roots with high speci c root length (SRL) and low root diameter or root tissue density (RTD) are often associated with high root turnover and short life span, and reduce the colonization of root-associated microbes (Bergmann et al 2020;Qiu et al 2021). Recent studies, however, explored the relationships between root traits and soil biota focus on microbes, such as bacteria and fungi (Spitzer et al 2021;Sweeney et al 2021), while it remains largely unknown how root traits affect soil fauna and the soil food web.…”
Section: Introductionmentioning
confidence: 99%